PENGARUH SELF EFFICACY TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DI SMA HARVARD - Winmery Lasma Habeahan; Meilisa Malik; Muhammad Huda Firdaus (MES: Journal of Mathematics Education and Science, 2023)
The aim of this study was to determine the effect of students' self-efficacy on the mathematical creative thinking abilities of students at Harvard High School. The subjects in this study were students of class X-IPA 1 which consisted of 20 students. This research is a true experiment research, with a one group pretest-posttest research design. Data collection was carried out through an instrument test for mathematical creative thinking ability and a non-test instrument test in the form of a self-efficacy questionnaire. Data analysis techniques were carried out through the Independent Sample t test using the SPSS application. The results of the study show that: There is an effect of self-efficacy on the ability to think creatively at Harvard High School